(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
The strength and shrinkage of concrete that is combined with sugarcane bagasse ash particles are influenced by the size of the particles, as analyzed in this research article. A higher amount of water is required when utilizing Sugarcane Bagasse Ash (ScBA) in concrete. The strength of the mixture created with fine ScBA can be comparable to or greater than that of standard concrete. The ScBA waste produced from sugarcane contracts substantially as a consequence of the presence of minute components within it. In this study, the researchers utilized a material known as Sugarcane Bagasse Ash (ScBA) to substitute cement in concrete. The experiment involved testing the effectiveness of ScBA (at different percentages: 0%, 5%, 10%, 15%, and 20%) in strengthening M20 concrete over a period of 28 days. They compared it to regular concrete. The extent to which it could resist pressure and strain without snapping was measured. The reason behind burning Sugarcane waste (ScBA) for fuel is its ability to produce significant amounts of heat. Cement can be supplemented with the remaining ash after it has been burnt.